Ghana gender strategy: Building equitable climate-resilient African bean and insect sectors - Acheampong, Patricia; Yeboah, Stephen; Fening Kennedy, Okwae; Asibuo, James; Lutomia, Cosmas; Ouya, Frederick; Ketema, Dessalegn; Nchanji, Eileen (2025)
Agricultural productivity in developing countries remains low due to non-improved farming practices, land degradation due to over-exploitation, poor enhancement of services such as agricultural extension, inadequate market access, and climatic factors such as droughts and floods (Belay et al. 2017). There is also the overriding influence of complex social and economic systems that impede agricultural production. The role of gender in agricultural production and subsequent productivity is key to consider. Women contribute significantly to agricultural production, yet they lack access to productive resources such as land, finance, and modern inputs (Doss & Meinzen-Dick, 2020). Gender inequalities in land ownership and financial access restrict women’s ability to invest in improved farming technologies, limiting their productivity (FAO, 2021). Youth, on the other hand, face barriers in accessing agribusiness opportunities, capital, and agricultural extension services (Jayne et al., 2022). Without targeted support, these groups remain marginalised in agricultural decision making and market engagement, limiting their ability to fully benefit from the sector. The fruit tree, bean and insects value chain holds great potential for improving food security and economic opportunities for smallholder farmers (Abate et al., 2012). Despite this potential, smallholder farmers, especially women and youth, continue to face disproportionate challenges that limit their productivity and income (Huyer, 2016). These groups face restricted access to financial resources, limited market linkages, and inadequate technical support, preventing them from adopting innovative and sustainable farming practices in key agricultural sectors such as beans, fruit trees, and insect farming. Ghana’s Food and Agriculture Sector Development Policy 2008 stated that gender inequality in the agricultural sector undermined the achievement of sustainable agriculture development because programmes and projects are not systematically formulated around the different needs of women and men. The Medium-Term Agricultural Sector Investment Plan in 2013 also indicated that the approximate male to female coverage ratio of all projects mapped was two to one, and very few of the projects had gender inclusiveness as part of the areas of focus within project objectives (FASDEP II, 2008; METASIP, 2013). The need to address both practical and strategic needs of men, women and the youth, to improve their basic conditions and positions in society cannot be overemphasised (Gender Agricultural Development Strategy II, 2015). The project, building gender equitable resilience for adaptation to climate change across the bean crop and insect corridors to enhance food and nutrition in Sub-Sahara Africa (BRAINS) implemented in Ghana and 14 other countries in Sub-Sahara Africa intends to foster low-carbon, climate-resilient systems and economies in the bean, fruit trees, and insect value chains through; (a) enhancing climate resilience more equitably among women and youth farmers and value chain actors, (b) bringing adoption of climate-smart agriculture (CSA) technologies that boost climate resilience to scale across targeted production systems, and (c) building a pipeline of enterprises that are actively investing in carbon-neutral, climate-resilient, and gender-responsive business development in line with emerging climate finance sector goals.